2004
DOI: 10.2174/1570162043351246
|View full text |Cite
|
Sign up to set email alerts
|

Vpu: A Multifunctional Protein that Enhances the Pathogenesis of Human Immunodeficiency Virus Type 1

Abstract: The Vpu protein is the smallest of the proteins encoded by human immunodeficiency virus type 1 (HIV-1). This transmembrane protein interacts with the CD4 molecule in the rough endoplasmic reticulum (RER), resulting in its degradation via the proteasome pathway. Vpu also has been shown to enhance virion release from infected cells. While much has been learned about the function of Vpu in cell culture systems, its exact role in HIV-1 pathogenesis is still unknown. This has been primarily due to the lack of a sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…They act to increase the production of viral particles from various human cell types, including primary lymphocytes and macrophages, and can also stimulate the release of heterologous retroviral particles. The importance of this activity is suggested by the fact that intact Vpu open reading frames are maintained in AIDS patients, and studies of chimeric SIV/HIV infections in macaques have demonstrated that Vpu is essential for pathogenicity (22,50).…”
Section: Discussionmentioning
confidence: 99%
“…They act to increase the production of viral particles from various human cell types, including primary lymphocytes and macrophages, and can also stimulate the release of heterologous retroviral particles. The importance of this activity is suggested by the fact that intact Vpu open reading frames are maintained in AIDS patients, and studies of chimeric SIV/HIV infections in macaques have demonstrated that Vpu is essential for pathogenicity (22,50).…”
Section: Discussionmentioning
confidence: 99%
“…Specific interaction of Vpu TM with hu-tetherin. HIV-1 Vpu protein consists of two major elements: an N-terminal TM domain that anchors Vpu in the cellular membranes and a CT consisting of two putative ␣-helices separated by a conserved phosphorylation site (21). To understand which domain of Vpu interacts with hu-tetherin, we generated HEK 293 cells stably expressing KGC-tagged hu-tetherin (KGC-hu-tetherin) (Fig.…”
Section: Fig 2 Interaction Of Tetherin and Vpu Via Tm Domains (A)mentioning
confidence: 99%
“…2A). Vpu is an 81-amino-acid HIV-1 regulatory protein involved in late processing of the HIV-1 virion, prior to release of free virus from CD4 T cells, and prevents Env from binding to the CD4 T-cell receptor within the endoplasmic reticulum during processing (5,11). The Vpu peptide pool is comprised of 19 overlapping peptides.…”
Section: Cd3mentioning
confidence: 99%